Accounting for colonial complicities through Refusals in researching agency across borders. (22nd August 2021) - Coultas, Clare
Abstract: Eve Tuck and K. Wayne Yang develop the concept of "refusal" as an essential methodology for decolonizing social sciences, that I suggest provides an opening for white scholars to contribute to decolonizing projects. In this article, I reflect on my attempts at engaging with my colonial complicities, as a white European woman doing research on comprehensive sexuality education and young people's agency in Tanzania. I present this discussion as a series of refusals interspersed throughout more conceptual discussions on how feminist and social psychological theorizing, and post‐/de‐colonial problematizations of it, have advanced my understanding of agency, and shaped my approach and research design. In drawing these literatures together, along with my own practical efforts at applying them, I attempt to mark out, but also problematize, potentials for white people's anti‐colonial praxis in working across borders. I conclude with some broad thoughts on the particularities of refusals connected to whiteness and the neoliberal university.